RESEARCH OF CORROSIVE DAMAGE TO THE PURPOSE OF FOOD PRODUCTION - Бойко, Андрій Васильович; Кулик, Василь Петрович; Макаренко, Валерій Дмитрович; Тараборкін, Леонід Анатолійович (Problems of Friction and Wear, 2019)
Chemical and food processing environments contain chemically active ingredients such as oxygen, carbon dioxide (СО2), carbon monoxide (CO), sulfur, hydrogen, carbon acid ion and sulfuric acid ion, chlorine ions, impurities of calcium carbonate, iron, and hydrochloric acid, etc. All these factors lead to intensive corrosion of the equipment, reducing its reliability and durability. The corrosion-mechanical resistance of metal equipment, such as chemical and sugar plants, is of great importance for environmental and sanitary requirements that make it impossible to contaminate the product with metal ions. First of all, the tubes of evaporation stations, diffusion apparatuses and steam boilers of chemical and agro-processing (sugar) enterprises are exposed to corrosive damage caused by the negative influence of high-temperature and corrosive-active steam under high pressure. Significantly worsens this negative situation and deposition of sediments of salts, carbonates, acids, and others. The analysis of corrosives damages suggests that predominantly point and pitting corrosion predominate, which are exacerbated by internal or external loads. Unlike uniform corrosion, finding and slowing down which is not a particular difficulty, these types of corrosion are usually detected only after they are caused by emergency failures or fractures. Therefore, the main reasons for failures of technical facilities, among which the important placeis the destruction or operation of corrosion and corrosion and mechanical damage, must be carefully investigated and, if possible, eliminated on time. The complex of investigations of the damaged metal of evaporator tubes (steel 20 and 06X1) with a life time (from 0 to 20 years) included, along with standard, also special types of research, in particular: various variants of X-ray spectral analysis using a raster electron microscope "JSM-35CF" (Jeol, Japan),"SEM-515" with Philips microinalyzer "Link" scanning Auger electron spectroscopy (micro-analyzer "AES-2000"). In addition, the content and character of the distribution in the metal of pipes of water heaters of hydrogen, sulfur and oxygen were determined by the method of local mass spectral analysis with a laser microprobe, as well as by the method of melting of metal samples in the flow of carrier gas using the installation of the firm "Leco". With the help of high-precision metallographic experimental equipment, the mechanism of corrosion damage to the surfaces of evaporator tubes and the proposed measures for further research on methods for reducing the corrosion activity of the process environment and the adhesion of salt and carbonate sediments to the surface of the tubes of steam generators of food production is investigated. In particular, it has been shown that in order to eliminate metal corrosion and deposits of salt sediments in the form of scale on the surface of pipes of water heaters, it is necessary simultaneously to reduce the chemical activity of the water-vapor environment using different reagents, and to cover the tube with anticorrosive protective.